195 MS disease modifying therapy (DMT) sequencing – tysabri to mavenclad de-escalation in JC-virus positive MS patients. Issue 12 (14th November 2019) - Mihalova, Tatiana; Vernon, Karen; Sharaf, Nazar; Talbot, Paul; Rog, David
Abstract : Background: There is a significant UK variation in the DMT sequencing strategies for high PML risk patients on Tysabri. In Greater Manchester Neuroscience centre we gradually reduced the number of high PML risk patients on Tysabri from 89 in 2016 to 26 in 2018. From our experiences de-escalation strategy from Tysabri to Fingolimod or Lemtrada seemed safe. Fingolimod, less efficacious switch, tends to be delivered quicker than Lemtrada (requiring lesser safety checks), but the efficacy of Lemtrada in MS patients with disease duration >10 years remains uncertain. Method: Between January 2018 and November 2018 we switched 14 high risk PML patients from Tysabri to Mavenclad. All patients underwent MDT discussion, lumbar puncture with JCV PCR and MRI checks prior to DMT switch. Results: We present the first UK MS patient cohort de-escalating from Tysabri to Mavenclad. Older (average age of 44) and more disabled patients (average EDSS=4.75) opted for Mavenclad, with equal gender distribution (7:7). Average disease duration was 7.5 (2–10) and patients received 52 (6–107) Tysabri infusions. 5 patients had other DMTs prior to Tysabri (5 Copaxone, 1 Rebif, 1 Tecfidera), 9 patients had Tysabri as their first DMT. Average JC-virus serology titer was 1.86. Conclusion: Switching high PML risks patients from Tysabri to Mavenclad appears to be well tolerated; regular MRI monitoring showed no PML carry-over risk and no significant MS disease activity.